P256 The effect of self-efficacy on return-to-work outcomes for workers with psychological or upper-body musculoskeletal injuries: a review of the literature. (1st September 2016) - Black, Oliver; Keegel, Tessa; Sim, Malcolm; Collie, Alexander; Smith, Peter
Abstract : Introduction: Work absence can result in substantial losses to the economy and workers. As a result, identifying modifiable factors associated with return-to-work (RTW) following an injury or illness is the focus of many empirical investigations. Self-efficacy, the belief about one's ability to undertake behaviours to achieve desired goals, has been identified in some studies as an important factor in RTW for injured workers. The literature on this relationship has not been systematically reviewed. This paper systematically reviews the literature on the association between self-efficacy and RTW outcomes for workers with an upper-body musculoskeletal injury or psychological injury. Methods: A systematic search was conducted across five databases using two main search concepts- 'self-efficacy' and 'RTW'. After removing duplicates, our search strategy identified 761 publications, which were screened for relevance using titles and abstracts. Results: Three publications using psychological injury cohorts and three using upper-body musculoskeletal (UB-MSK) cohorts from five prospective cohort studies were retained following screening. Higher levels of self-efficacy appeared to have a consistent and positive association with RTW across return-to-work status and work absence outcomes, injury type and follow-up period. The relationship between self-efficacy and RTW strengthened as the domain of self-efficacy became more specific to RTW behaviours. Publications assessing workers with psychological injuries were of a lower quality compared to those assessing workers with upper-body musculoskeletal injuries. Conclusions: Higher self-efficacy had a consistent positive associations with RTW outcomes. Further empirical research should identify the determinants of self-efficacy, and explore the processes by which higher self-efficacy improves RTW outcomes.